The Effect of using social media networks on the academic achievement of student in tripoli city - Shuayb, Ayman; Gebreel, Omar Salem Seed (Pakistan Review of Social Sciences (PRSS), 2021)
This study is conducted to examine the effect of using social media networks on the academic achievement of students in Tripoli city from the view of housewives. It was also to Identifying the positive and negative effects of using social media networks on students’ academic achievement, Identifying the main reasons why students using social media networks, and Identifying the most common hours that students use social media networks and try to link them to the nature of use. The study used the descriptive approach and employed the questionnaires to collect the data from 223 housewives in Tripoli city. The researcher used the data analysis software SPSS v.22 for the purpose of coding and analyzing the primary data. Results have shown that using social media from the students can be of a positive and effective impact on academic performance if it was used under the control of housewives. So that network users are not able to access them, and the necessity of rationalization, and the moderate use of the Internet by children and youth in order to achieve specific and clear objectives.